Carbon Stock Estimation in Small-Scale Peat Ecosystems Based on the NDVI Vegetation Index on the Google Earth Engine Cloud Computing Platform - Danarto, Wisnu Putra; Muhtar, Ghinia Anastasia; Fahmi, Hilman; Prasakti, Yogi; Yahya, Donny; Hasanah, Nur (Universitas Lambung Mangkurat, 2023)
Peatlands are wetland ecosystems that originate from piles of rotting organic material on the surface of the soil. Peatlands have unique conditions that are not found in other land system units, these conditions include having a high biomass value and carbon storage capacity. Jambu Baru Village is one of the villages located on a peatland unit with ecosystem conditions that have not experienced major changes or conversion of function. Field measurements aim to test and validate the value of soil biomass and carbon content in peatlands. The greenness index model from Sentinel 2A satellite imagery is used as the main basis for determining sampling plots for biomass measurements in each class of greenness index for each land cover in the field. The research results showed that the greater the diameter and height of the plant, the higher the biomass content and carbon stock, high stands obtained a biomass value of 14.95 kg with a carbon stock of 20.36 kg; medium stands obtained a biomass value of 9.08 kg with a carbon stock of 7.33 kg and low stands obtained a biomass value of 0.89 kg with a carbon stock of 0.42 kg. In this research, results were also obtained which showed that the tree and pole sources had the highest biomass among the other sources, 24.04 kg with 27.68 kg of carbon. The results of calculating biomass and carbon stock values for the wetland ecosystem in Jambu Baru Village are presented in spatial modeling in the form of a map of estimated biomass and carbon stock values.